Envisioning Clinical Management of Breast Cancer: a Comprehensive Review - Das, Shubhashree; Pattnaik, Gurudutta; Pattanaik, Sovan; Jena, Bikash Ranjan; Satapathy, Bhabani Sankar; Pradhan, Ayushi (Current Drug Discovery Technologies, 2025)
BackgroundBackground: Coming to the edge of disease manufacturing in the twenty-first-century, breast cancer occupies a terrifying scenario in the globe, especially in adult women. Its curiosity endeavours remarkable advances made during the past decennaries for cancer treatment and diagnosis.ObjectiveIt accounts for the fifth leading cause of transience, killing approximately 570,000 people per annum. To reduce the prognosis of clinical oncological development with the application of a new chemical entity, some of the critical challenges, like active pharmaceutical ingredients with high chemical resistance, extreme side effects, and high treatment costs are some of the limitations in the curbing aspects of breast melanoma.MethodsIn cancer research, hence, the development of drugs that are safe, efficient, and cost-effective remains a 'Holy Grail' that may be considered as a boon to target the malignant tissues with novel therapeutics devices.ResultsThrough the findings on overcoming the drawbacks of traditional methods, researchers have given special attention to cancer-preventive and theranostic approaches based on some novel drug delivery systems.ConclusionThe present study forecasts the wide-ranging modern applications, and on developing some novel liposomal drug delivery therapy against breast cancer.
Keywords: mammography